Assessing the effects of the Spanish partial smoking ban on cardiovascular and respiratory diseases: methodological issues. Issue 12 (1st December 2015) - Galán, Iñaki; Simón, Lorena; Flores, Víctor; Ortiz, Cristina; Fernández-Cuenca, Rafael; Linares, Cristina; Boldo, Elena; José Medrano, María; Pastor-Barriuso, Roberto
Abstract : Objective: Recent research has assessed the impact of tobacco laws on cardiovascular and respiratory morbidity. In this study, we also examined whether the association between the implementation of the 2005 Spanish smoking ban and hospital admissions for cardiovascular and respiratory diseases varies according to the adjustment for potential confounders. Design: Ecological time series analysis. Setting: Residents of Madrid and Barcelona cities (Spain). Outcome: Data on daily emergency room admissions for acute myocardial infarction, cerebrovascular disease, chronic obstructive pulmonary disease (COPD), and asthma derived from the 2003–2006 Spanish hospital admissions registry. Methods: Changes in admission rates between 2006 and the 2003–2005 period were estimated using additive Poisson models allowing for overdispersion adjusted for secular trend in admission, seasonality, day of the week, temperature, number of flu and acute respiratory infection cases, pollution levels, tobacco consumption prevalence and, for asthma cases, pollen count. Results: In Madrid, fully adjusted models failed to detect significant changes in hospital admission rates for any disease during the study period. In Barcelona, however, hospital admissions decreased by 10.2% (95% CI 3.8% to 16.1%) for cerebrovascular diseases and by 16.0% (95% CI 7.0% to 24.1%) for COPD. Substantial changes in effect estimates were observed on adjustment for linear or quadratic trend. Effect estimates for asthma-related admissions varied substantially when adjusting for pollen count in Madrid, and for seasonality and tobacco consumption in Barcelona. Conclusions: Our results confirm that the potential impact of a smoking ban must be adjusted for the underlying secular trend. In asthma-related admissions, pollen count, seasonality and tobacco consumption must be specified in the model. The substantial variability in effects detected between the two cities of Madrid and Barcelona lends strong support for a nationwide study to assess the overall effect of a smoking ban in Spain and identify the causes of the observed heterogeneity.